Digitalisasi Pelayanan Gereja Melalui Pengembangan Website Berbasis Design Thinking - Nata, Rudi; Delika (LPPM Universitas Dinamika Bangsa, 2025)
The rapid development of information and communication technology has triggered significant changes in various aspects of life, including the religious sector. The HKBP Agave Mendalo Darat Church faces challenges in effectively disseminating information to its congregation, especially for out-of-town students and members who cannot physically attend church services. Therefore, this research aims to design a web-based information system that includes features such as live-streamed worship services, digital worship materials, and online event registration. The study employs the Design Thinking approach with five main stages—empathize, define, ideate, prototype, and test—to create solutions that are relevant to user needs. Keywords: Digitalization, Ministry, Church, Website